Analysis of the Influence of Leadership and Compensation Through Work Discipline on Performance - KR, M. Yusuf Alfian Rendra Anggoro (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to analyze the influence of Leadership, Compensation and Work Discipline variables on Performance. Where this research uses quantitative and qualitative research. The population in this study was all 300 Madrasah Aliyah (MA) teachers in Barru Regency. This research used a sample of 171 teachers, this number is considered representative. Then the sampling method used was the proportional Stratified Random Sampling method. The data analysis techniques used to explain the phenomena in this research are descriptive statistical analysis techniques and Structural Equation Modeling (SEM) analysis. The results of this research show that: (1) Leadership has a positive and significant effect on work discipline, (2) Compensation has a positive and significant effect on work discipline, (3) Leadership has a positive but not significant effect on performance, (4) Compensation has a positive and significant effect on performance, (5) Work discipline has a positive and significant effect on performance, (6) Leadership through work discipline has a positive and significant effect on performance, (7) Compensation through work discipline has a positive and significant effect on performance.